Strategies for public health adaptation to climate change in practice: social learning in the processionary Moth Knowledge Platform - Buist, Yvette; Bekker, Marleen; Vaandrager, Lenneke; Koelen, Maria; van Mierlo, Barbara (Frontiers in Public Health, 2023)
Social learning theory can support understanding of how a group of diverse actors addresses complex challenges related to public health adaptation. This study focuses on one specific issue of public health adaptation: oak processionary moth (OPM) adaptation. With a social learning framework, we examined how public health adaption strategies gradually develop and are adjusted on the basis of new knowledge and experiences. For this qualitative case study, data were collected through 27 meetings of the Processionary Moth Knowledge Platform in the Netherlands and six additional interviews. Results indicate that relations between stakeholders, including experts played a major role in the learning process, facilitating the development and implementation of OPM adaptation and connecting local challenges to national adaptation strategies. Uncertainties regarding knowledge and organization were recurrent topics of discussion, highlighting the iterative and adaptive nature of public health adaptation.. The study emphasizes the importance of building relationships among stakeholders and small steps in the learning process that can lead to the creation of new strategies and, if successful, the prevention of negative health impacts.